ANALISIS TINGKAT PENDAPATAN PETANI JAGUNG DI DESA SALUMANG KECAMATAN MEMPAWAH HULU KABUPATEN LANDAK - Lintang, Fikasius; Witarsa, Witarsa; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The study was conducted in Salumang Village, Mempawah Hulu District, Landak Regency. This study aimed to determine: 1) The total corn farming production, 2) production costs, and 3) level of income in one growing season was evaluated. The study utilized a qualitative analysis method. The study involved five corn farmers as informants. Data collection was carried out using methods such as interviews, observations, and documentation. According to the results, the total corn production for five respondent farmers was 15,600 kg / hectare / growing season. The average total production was 3,120 kg / hectare / growing season. The total production costs incurred by farmers in Salumang Village were Rp. 19,992,000 / hectare / growing season. The average total production cost expenditure was Rp. 3,332,000 / hectare / growing season. The total income earned during one growing season was Rp. 58,008,800 / hectare / growing season. Additionally, the average total income was Rp. 11,601,760 / hectare / growing season.